Digital Transformation in the Validation of Land Tax Block Maps and Land Parcel Maps in Bojonegoro Regency - Budisusanto, Yanto; Soetedjo, Abid Mushthofa (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2025)
The digital era has brought significant changes across various sectors, including the management of Land and Building Tax (PBB) in Indonesia. As one of the country’s key revenue sources, a large portion of PBB is allocated to regional income, which supports public facilities provided by both central and local governments. Therefore, accurate and integrated taxation data is essential for fair and precise tax calculation. This study aims to evaluate and analyze the consistency between the Land and Building Tax (PBB) maps and the Land Parcel (PBT) maps in Kedaton Village, Kapas District, Bojonegoro Regency. The research identifies discrepancies in land area, the consistency of taxpayer and landowner names, and the spatial data quality between both map types. Spatial evaluation was conducted using Polygon Area, Polygon Near Distance, and Polygon Circularity Ratio methods to assess spatial accuracy, proximity between polygons, and shape regularity. The results show a 48% area discrepancy beyond the acceptable tolerance, and only 30% of parcels had matching taxpayer and landowner names. Based on PBT evaluation, 52% of parcels in the PBB map were categorized as accurate. The study recommends improving data integration between PBB and PBT maps to enhance taxation accuracy, land administration efficiency, and regional tax revenue optimization.